Novel flame retardant paint based on Co(II) and Ni(II) metal complexes as new additives for surface coating applications. (20th October 2020) - Younis, A.A.; Faheim, Abeer A.; Elsawy, M.M.; El‐Wahab, H. Abd
Abstract : The study is focused on the synthesis of a new Co(II) and Ni(II) metal complexes, which is synthesized by the reaction of the isatin 4‐aminoantipyrine Schiff base ligand with selected divalent Co(II) and Ni(II) ions and their possible applications as flame retardant additives in paint formulations for surface coating application. The prepared metal complexes were characterized using a combination of Fourier transform infrared, elemental analysis, proton nuclear magnetic resonance, 13 C‐NMR spectra, and mass spectroscopy. The prepared Schiff base ligand metal complexes were physically added to alkyd paint formulation to give coating formulations at a laboratory scale and then applied onto plywood and steel panels using a brush. The ignitability and oxygen index values obtained indicated that the paint which contained the prepared Co(II) and Ni(II) metal complexes as additives exhibited very good flame retardant. The physical and mechanical characteristics of the coatings were studied in order to estimate any disadvantages due to the incorporation of the additives. It was discovered that the added substances did not impact the hardness, flexibility, and adhesion of the prepared coating films. The gloss of the paint formulation film was improved due to the incorporation of the aromatic ring into the formulation and the level of the oil percent. Abstract : Preparation and evaluation of new organic metal complexes as fire retardant for surface coating applications, the prepared compounds were characterized by different analysis and based on the tabulated and presented results, their enhancement of the mechanical, ignition properties of the coated specimens were observed.